Senescence, aging, and malignant transformation mediated by p53 in mice lacking the Brca1 full-length isoform - Liu Cao; Wenmei Li; Sang Soo Kim; Steven G. Brodie; Chu‐Xia Deng (2003)
Senescence may function as a two-edged sword that brings unexpected consequences to organisms. Here we provide evidence to support this theory by showing that the absence of the Brca1 full-length isoform causes senescence in mutant embryos and cultured cells as well as aging and tumorigenesis in adult mice. Haploid loss of p53 overcame embryonic senescence but failed to prevent the adult mutant mice from prematurely aging, which included decreased life span, reduced body fat deposition, osteoporosis, skin atrophy, and decreased wound healing. We further demonstrate that mutant cells that escaped senescence had undergone clonal selection for faster proliferation and extensive genetic/molecular alterations, including overexpression of cyclin D1 and cyclin A and loss of p53. These observations provide the first in vivo evidence that links cell senescence to aging due to impaired function of Brca1 at the expense of tumorigenesis.